2021
DOI: 10.1021/acscatal.1c00896
|View full text |Cite
|
Sign up to set email alerts
|

Side Chain Conformation Restriction in the Catalysis of Glycosidic Bond Formation by Leloir Glycosyltransferases, Glycoside Phosphorylases, and Transglycosidases

Abstract: Carbohydrate side chain conformation is an important factor in the control of reactivity at the anomeric center, i.e. in the making and breaking of glycosidic bonds, whether by chemical means or, for hydrolysis, by glycoside hydrolases. In nature glycosidic bond formation is catalyzed out by glycosyltransferases (GTs), glycoside phosphorylases, and transglycosidases. By an analysis of 118 crystal structures of sugar nucleotide dependent (Leloir) GTs, 136 crystal structures of glycoside phosphorylases, and 54 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“… [8] The rate of glycoside hydrolysis was found to be gg > gt > tg , as corroborated in the galacto series by our laboratory [9] . In addition, our recent findings have revealed that the influence of side chain conformation on reactivity is exploited by nature, where many GHs and GTs bind their ligands with specific side chain conformations [13, 14] . For example, >80 % of glucosidases restrict the side chain of glucose in their active sites to the gg conformation: considering the ≈50 : 50 unbound population of gg : gt conformers, these enzymes appear to have evolved to take the advantage of the substrate side chain conformation to gain additional transition state stabilization [13] .…”
Section: Figurementioning
confidence: 53%
“… [8] The rate of glycoside hydrolysis was found to be gg > gt > tg , as corroborated in the galacto series by our laboratory [9] . In addition, our recent findings have revealed that the influence of side chain conformation on reactivity is exploited by nature, where many GHs and GTs bind their ligands with specific side chain conformations [13, 14] . For example, >80 % of glucosidases restrict the side chain of glucose in their active sites to the gg conformation: considering the ≈50 : 50 unbound population of gg : gt conformers, these enzymes appear to have evolved to take the advantage of the substrate side chain conformation to gain additional transition state stabilization [13] .…”
Section: Figurementioning
confidence: 53%
“…In recent years, it has become increasingly apparent that the conformation of the side chain of glycosyl donors contributes significantly to their reactivity and selectivity, with the initial ground rules determined using conformationally locked bicyclic donors. More recently, we have demonstrated by the study of a series of sialic acid and Kdo donors isomeric at the 5- and/or 7-positions that side-chain conformation also contributes to reactivity and selectivity in monocyclic donors (Figure ). Finally, recent studies have highlighted the role of side-chain conformation in glycan recognition and as a contributing factor to catalysis by the glycosyl hydrolases, glycosyltransferases, transglycosidases, and glycoside phosphorylases during enzymatic cleavage and the formation of glycosidic bonds …”
Section: Introductionmentioning
confidence: 99%
“…model allowed unambiguous assignment of the solid state molecular structure and absolute configuration. As shown in Figure 2, the desired axial anomeric phosphate was clearly visible alongside an interesting gg rotameric form for the C6-chloro side chain substituent (pyranose side chain conformation has recently been shown to be an important factor contributing to anomeric reactivity of canonical pyranoses [12]). One phenyl ring of the phosphate ester group occupied a position folded underneath the pyranose ring and engaged in an intramolecular C-H•••π interaction with the axial C5 proton (Figure 2, dotted line).…”
Section: Resultsmentioning
confidence: 93%